The llamas of Choquequirao, Cusco Imperial Art of the 15th Century - Echevarría López, Gori Tumi (2010)
A systematic exploration in the archaeological site «Choquequirao», Cusco, Peru, has produced in the year 2004 the finding of a group of naturalists and geometric motifs that were drawn with stones on a sector of terraces in this important site; a settlement located next to the Apurimac river in the Amazonian - Andean limit of the mountain range of the Andes. This finding opened the possibility of developing a comprehensive and controlled investigation in these archaeological materials, which were developed in the year 2005. Part of the carried out analyses included technical approaches from the artifact theory, and historical correlations. This paper expose the particular analysis of the naturalist motifs stressing the proposition of the artistic nature, and the cultural and chronological association of these motifs.